2014
DOI: 10.1093/ehjci/jeu143
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic findings in simple and complex patent foramen ovale before and after transcatheter closure

Abstract: In our series of patients, the closure rate was dependent on PFO morphology more than occluder size and type. An adjunctive device was implanted in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
2
42
0
2
Order By: Relevance
“…Meissner et al reported the risk of paradoxical embolism was several times higher in patients with ASA regardless of a diagnosis of PFO . Furthermore, the presence of ASA has been associated with lower rates of successful closure and higher residual shunting at follow‐up, which was attributed to probable relative instability of the PFO device . However, due to its low prevalence in CS patients, the usefulness of ASA as a marker for selecting high risk patient that might benefit from PFO closure is undetermined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meissner et al reported the risk of paradoxical embolism was several times higher in patients with ASA regardless of a diagnosis of PFO . Furthermore, the presence of ASA has been associated with lower rates of successful closure and higher residual shunting at follow‐up, which was attributed to probable relative instability of the PFO device . However, due to its low prevalence in CS patients, the usefulness of ASA as a marker for selecting high risk patient that might benefit from PFO closure is undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, the presence of ASA has been associated with lower rates of successful closure and higher residual shunting at follow-up, which was attributed to probable relative instability of the PFO device. 21 However, due to its low prevalence in CS patients, the usefulness of ASA as a marker for selecting high risk patient that might benefit from PFO closure is undetermined. In our 158 study subjects, the prevalence of ASA was only 7.6%…”
Section: Optimal Patient Selection For Pfo Closurementioning
confidence: 99%
“…Few studies on PFO closure were performed using the Occlutech Figulla ® devices, and to our knowledge no reports on the third generation Figulla ® Flex II PFO Occluder are available [15, 18–20, 2224]. …”
Section: Discussionmentioning
confidence: 99%
“…The foramen ovale, on the right side of the septum, is entirely covered by its valve that pertains to the left atrial wall. Vitarelli et al recently published findings in patients with simple and complex patent foramen ovale before and after transcatheter closure . They found that a number of anatomic atrial variations, besides atrial septal aneurysm, impact percutaneous patent foramen ovale closure.…”
Section: Right Atrial Anatomymentioning
confidence: 99%
“…Vitarelli et al recently published findings in patients with simple and complex patent foramen ovale before and after transcatheter closure. 18 They found that a number of anatomic atrial variations, besides atrial septal aneurysm, impact percutaneous patent foramen ovale closure. In addition, they revealed that success of the occlusion, determined by the absence of residual shunting on contrast twodimensional TEE, was significantly associated with the morphologic features of the atrial septum.…”
Section: Introductionmentioning
confidence: 99%